Humates mitigate Cd uptake in the absence of NaCl salinity, but combined application of humates and NaCl enhances Cd mobility & phyto-accumulation - Ondrasek, Gabrijel; Romić, Davor; Tanaskovik, Vjekoslav; Savić, Radovan; Rathod, Santosha; Horvatinec, Jelena; Rengel, Zed (Elsevier BV, 2022)
Cadmium is among the critical pollutants easily taken up from contaminated media by plants, which can be exploited in the phytoremediation of Cd-contaminated resources, but is also an obstacle in producing food with low Cd content. Crucial variables governing Cd biogeochemistry are complex humates (HA) and chlorides, but the underlying interactions are poorly understood. The aim was to determine the impacts of HA (0-60 mg/L) and NaCl (0-30 mM) on Cd biochemistry in contaminated (2.0 μM Cd) rhizosphere solution and Cd accumulation in various tissues of strawberry (Fragaria x ananassa). The results show that salinity (vs. non-saline NaCl0 control) suppressed vegetative and yield parameters, but increased dry matter and Na, Cl and Cd concentration/accumulation in most of the analysed tissues. The HA application in the NaCl0 treatment decreased tissue Cd content; however, at the highest application rates of NaCl and HA, there were increases in the tissue Cd concentration (by 70 %, 100 % and 120 % in crowns, leaves and fruits, respectively) and accumulation (by 110 %, 126 % and 148 % in roots, fruits and leaves, respectively) in comparison to the control (NaCl0HA0). Tissue Cd concentration/accumulation decreased in the order: roots>crowns>leaves>fruits; the same accumulation pattern was noted for Na and Cl, suggesting that Cd-Cl complexes may represent a major form of Cd taken up. Chemical speciation calculations revealed that the proportions of various Cd forms varied multi-fold across the treatments; in the control (without NaCl and HA), Cd2+ dominated (86 %), followed by CdHPO4 (6.5 %), CdSO4 (6.2 %) and CdNO3+. In other treatments the proportion of Cd2+ decreased with a corresponding increase of Cd-Cl (from 0.02 % in control to 57 % in Cd + NaCl30 treatment) and Cd-HA (from 0 % in control to 44 % in Cd + HA60 treatment), which was associated with higher Cd phytoaccumulation. The results represent a theoretical basis for phytoremediation studies and for producing low-Cd food in relatively complex matrices (contaminated soils, reused effluents); in the absence of salinity, amelioration with humates has a great potential to mitigate Cd contamination.